Serial Resonant Converter and Load Coil for High Frequency Heating - Ocilka, Matus; Kovac, Dobroslav; Kovacova, Irena; Perdulak, Jan; Gladyr, Andrii; Mamchur, Dmytro; Zachepa, Iurii; Vince, Tibor; Molnar, Jan (Communications - Scientific letters of the University of Zilina, 2013)
The paper deals with the design of the voltage source half-bridge resonant inverter with the specific load coil, which is suitable for induction heating applications. To ensure the correct functionality and right frequency range of the self-resonant converter, the parameters as inductance, self-capacitance and resistance of the coil have to be obtained. Parameters of the coil are estimated by utilizing software that uses finite elements method of solution. In order to estimate the accuracy of model, the experimental verifications were taken. For this purpose, the spiral coil made on printed circuit board was created and its parameters were calculated, simulated and compared with measurement results.